Towards graft-versus-host disease-free alternative donor transplant platforms for patients with acquired aplastic anemia - Joseph H. Oved; Andrea Bacigalupo; Amy E. DeZern (Haematologica)
Hematopoietic stem cell transplantation is a well-established treatment option for acquired aplastic anemia. Historically, upfront hematopoietic stem cell transplantation (HCT) with HLA-matched sibling donors is used in young patients and immunosuppressive therapy (IST) is used for all others. Over time, innovations in the transplant platform have decreased unwanted complications such as graft versus host disease (GVHD), failure to engraft, and infections thereby expanding the use of alternative donors. This has led to an evolution towards HCT and away from IST despite increased intensity of treatment due to improved event free survival. The ideal conditioning regimen for HCT in aplastic anemia results in sustained engraftment, minimal toxicity, lack of GVHD and is not limited by donor availability. Two transplant platforms have been refined to meet these needs. TCR αβ+ T cell depletion has excellent outcomes with minimal graft-rejection and GVHD in the matched and mismatched unrelated donor setting. Haploidentical grafts however still require further optimization. Bone marrow grafts given with ATG and post-transplant cyclophosphamide have similarly excellent results with extremely low rates of GVHD. Peripheral mobilized grafts need further optimization in this setting. This review provides an overview of the current perspective on regimens that minimize GVHD in aplastic anemia and how they can be further refined so that all patients with aplastic anemia have curative therapy available to them.